The Role of Kindergartens in enhancing the Values of Citizenship to Child of Kindergartens from the Teachers' point of view Afield Study in Tartous - Hmaedoosh, Anwar; Nassor, Ragda; Suleiman , Madlen (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aimed to recognize the role of kindergartens in enhancing the values of citizenship to child of kindergartens from the teachers' point of view in Tartous city, through recognize the role of the kindergarten teacher in reinforcement citizenship in Tartous governorate, and identify the role of curriculums in reinforcement citizenship, and identify role of activities in reinforcement citizenship, researcher used descriptive analytic method the study tool questionnaire consist of (72) paragraph. This tool was applicated on a sample of (182) teachers during the 2017-2018. The results of the questionnaire were analyzed, using the mathematical averages, relative weights, and (T-Test, One Way ANOVA, Scheffe) tests. To validate the tool, it was presented to a panel of seven (7) specialists. The instrument was validated by pilot administration to a random sample of (32) kindergarten teachers, Cronbach's Alpha equation that which reach (0.97), and (0.98) in Spearman, Brown. The research results showed that the role of the kindergartens in enhancing the values of citizenship to child of kindergartens in Tartous city came of a medium degree. Also it was shown that there were no differences of statistical indication about the role of the the kindergartens in enhancing the values of citizenship to child of kindergartens in Tartous city from the teachers' point of view according to the variable the authorities supervising), while statistical significant different according to the variable experience in favor of the higher experience. The research provided some suggestions such as enhancing the Values of Citizenship to Child of Kindergartens (work to develop proactive spirit between children, and encourage children to dialogue using technological innovations), also training the kindergarten teachers on citizenship concepts.